Itinerários terapeuticos no pré-natal em comunidades rurais do interior do Amazonas - um estudo qualitativo - Carvalho, Andréa Regina Martins de (2022)
Quality prenatal care is critical to maternal and newborn health. The main objective of prenatal care is to welcome the woman from the beginning of pregnancy, ensuring the birth of a healthy child and ensuring maternal and neonatal well-being. It is important to understand the types of connection between women living in non-urban areas and health services, given the importance of prenatal care and seeking to understand the view that women living in rural areas have about it. The concept of Therapeutic Itineraries allows us to understand the paths traced and paths taken by pregnant women in their search for access to prenatal care. To better understand the dynamics of care during pregnancy, it is useful to understand the paths used in the search for prenatal care and to reflect on this search. The objective of this research is to understand the therapeutic itineraries for performing prenatal care in rural communities in Itacoatiara, in the interior of Amazonas. This is a qualitative descriptive and exploratory study. For data collection, the semi-structured interview instrument applied by the researcher was used. The research subjects were post partum women living in rural communities in the municipality of Itacoatiara, in Amazonas. The collected data were transcribed and analyzed using the content analysis technique proposed by Bardin, where it was possible to establish three categories of analysis. Of the post partum women invited to participate in the survey, only one refused. Then, 6 interviews were carried out. The age of the interviewees ranged from 18 to 40 years. In rural areas, the difficulties in seeking health care services are greater because this means presents gaps in relation to health care. In addition to the production of a Guide for CHAs, who are the professionals who best and most frequently move through the territory, this study and its local dissemination also resulted in a discussion between the professionals of the health team and the manager of the UBS during the project's formulation